USING ANNOTATING TEXT STRATEGY TO IMPROVE READING COMPREHENSION ON REPORT TEXT OF THE ELEVENTH GRADE STUDENTS OF SMA NURUL IMAN PALEMBANG - Manurung, Jenny Elvinna; Syaputri, Heti (JURNAL DIDASCEIN BAHASA, 2018)
ABSTRACT: The aimed of this research was to find out whether the use of Annotating Text Strategycould help teacher or not in teaching and learning process, especially in teaching report text. There were 58 students of eleventh grade SMA Nurul Iman Palembang in academic year 2016/2017. They were divided to be two groups, experimental (29 students) and control group (29 students). In this study, the writers used Non-equivalent group design. We taught the experimental group students to read a report text by using Annotating Text Strategy. Meanwhile, we taught the control group students to read a report text by using lecturing method. The data from two groups were collected from the results of pre-test and post-test scores which were analyzed to get mean score differences. The writers find out that mean score of the experimental group improved significantly from 54,48 pre-test to be 74,14 in post-test. Based on the independent sample t-test analysis, it was found that the significant level was 0,04< 0,05. It meant that there was any significant difference in reading comprehension between students who were taught by using Annotating Text Strategy and those who were not. Keywords: reading comprehension, report text and annotating text strategy.